(untitled) (SCIENCE TIME JOURNAL, 2026)
Lexical deviation is a main concept of stylistics which refers to the usage of words in non-standard or unconventional manner for specific purposes. This article describes the phenomenon of lexical deviation. It examines its theoretical foundations, primary types and its functions within literary texts. These studies express how authors break language structures in order to achieve an aesthetic impact in literary work.